Determination of quality of chicken eggs what were produced in «Poltava Poultry Factory» - Щербакова, Н. С.; Передера, Ж. О.; Передера, С. Б. (Scientific Progress & Innovations, 2015)
In the articles we gave data, that show the indexes of quality and safety of chicken eggs that is produced by Privately Joint Stock Society «Poltava poultry factory». Eggs are investigated on content of toxic elements of suchas: lead, cadmium, mercury, copper, zinc, arsenic, and also antibiotics. Content of fat in yolk and carotenoids. Organoleptic studies and egg tester are undertaken. It is set that eggs are chicken that came from PJSS the "Poltava poultry factory" on the indexes of quality answers the indexes of operating normative documents.